Respuesta :

Answer:

1(a) = 10

1(b) = 9

1(c) = 12

2(a) = 8

2(b) = 10

2(c) = 1

Step-by-step explanation:

1(a) = 22 - 2.6

     = 22 - 12 = 10

1(b) = 6 - 1/4 . 16 + 21 / 3

     = 6 - 16/4 + 7

     = 6 - 4 + 7

     = 9

1(c) = (8-5). (5-3)^2

     = 3*2^2

     = 3*4

     = 12

2(a) = 4(x-2)/(x-1) when x = 0

       = 4(0-2)/ (0-1)

       = 4*-2/-1

       = -8 / -1

       = 8

2(b) = (-3x^2 + 4) / 4 when x = -2

       = (6^2 + 4) / 4

        = (36 + 4) / 4

       = 40 / 4 = 10

2(c) = [-2x/4 + 4*(x-1)] / x^2 - 1 when x = 2

      = (-1 + 4 * 1) / 4 - 1

      = 3 / 3

      = 1

         

1) a. 10
b. 9
c. 12

2) a. 4(x-2) / (x-1)
= 4(0-2) / (0-1)
= 4(-2) / (-1)
= -8/-1
= 8
b. -3x^2 + 4 / 4
= -3(-2)^2 + 4 / 4
= -3(4) + 4 / 4
= -12 + 4 / 4
= -8 / 4
= -2
c. [-2x/4 + 4 (x-1)] / x^2 - 1
= [-2(2)/4 + 4 (2-1)] / 2^2 - 1
= [-2(2)/4 + 4(1)] / 2^2 - 1
= [-2(2)/4 + 4(1)] / 4 - 1
= (-4/4 + 4)/ 4 - 1
= (-1 + 4) / 4 - 1
= 3 / 3
= 1